2005
DOI: 10.1038/sj.jhh.1001946
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cerebral blood flow by single-photon emission computed tomography in young Asian Indians with hypertension

Abstract: The objective of the study was to investigate abnormalities of regional cerebral blood flow (rCBF) in young (age 33.076.3 years; range 21-45 years) non-diabetic and normolipidemic Asian Indians with hypertension. The rCBF was assessed with single-photon emission computed tomography (SPECT) in patients with hypertension (n ¼ 33) and healthy controls (n ¼ 20). The SPECT findings were normal in 41 subjects and showed abnormalities of cerebral perfusion in 10 subjects, all of which were hypertensive patients. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…11 Previous studies have noted brain hypoperfusion in hypertensive subjects, even those subjects with no neurologic symptoms. 1,2 The most vulnerable CBF regions in persons with hypertension vary. The reduction in regional CBF is most marked in the frontal and temporal lobes 1 or in the upper frontal, posterior parietal, and occipital regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Previous studies have noted brain hypoperfusion in hypertensive subjects, even those subjects with no neurologic symptoms. 1,2 The most vulnerable CBF regions in persons with hypertension vary. The reduction in regional CBF is most marked in the frontal and temporal lobes 1 or in the upper frontal, posterior parietal, and occipital regions.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral blood flow (CBF) is disturbed in hypertensive patients with no previous history of stroke. [1][2][3] Angiotensin II receptor blockers (ARBs) are used widely to treat hypertension. Recently, the protective effects of ARBs on target organs also have received attention.…”
mentioning
confidence: 99%
“…Additionally, hypertension has been associated with reduced regional cerebral blood flow in healthy adults at rest (Meyer et al, 1985; Sinha et al, 2005). One previous study that used 15 O-water tracer PET to measure regional cerebral blood flow found that hypertensive participants had reduced overall cerebral blood flow compared with normotensive participants (Jennings, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistency in results possibly arises due to differences in the use of subjective visual rating scales to assess the extent of pathology across groups, regional focus of disease (global versus focal), in addition to differences in enrolment criteria and the type and severity of vascular disease across imaging cohorts. Indeed, different vascular disease factors are associated with varying types and levels of pathology: hypertension has been associated with reduced cerebral blood flow [83] and an increased risk of periventricular white matter lesions [84,85]; lower arterial oxygen saturation and chronic obstructive pulmonary disease have been associated with cerebral white matter lesions, but not lacunar infarcts [86]; diabetes has been associated with cortical and hippocampal atrophy [87,88], white matter lesions [89] and lacunar infarcts [89]; and current smoking status, diabetes and hypertension are associated with both neurodegenerative (that is, decreased brain volume) and vascular (that is, lacunar infarcts and white matter lesions) changes [90]. …”
Section: Defining the Boundary Between Vcind And MCImentioning
confidence: 99%